Potensi Pengembangan Usaha Ayam Kampung di Nagari Durian Gadang, Kecamatan Sijunjung, Kabupaten Sijunjung - Hera Dwi Triani Triani; Afrini Dona; Sofia Tunnengsih; Fadilla Meidita (Program Studi peternakan, 2022)
The people in Nagari Durian Gadang Sijunjung District Sijunjung Regency is a mountainous area. Utilization can be used as waste so as to increase the population of native chickens in the Nagari. Nagari Durian Gadang, where most of the people work as farmers so that a lot of agricultural waste that can be used as chicken feed. This study uses a survey method by collecting information from all native chicken in Nagari Durian Gadang who meet the criteria. The Data used are primary data and secondary data. The results showed that the population native chicken in Nagari durian Gadang is still small (315 chick). Characteristics of native chicken farmers in Nagari durian Gadang average productive age (91.18%), the dominant sex is female (52.94%). The level of education in general is elementary/equivalent (50%) with experience raising for 1-5 years (88.24%) and semi-intensive maintenance system. Based on the results of the study it can be concluded that the characteristics of native chicken average productive age with a dominant female sex. The level of education of breeders is generally elementary/equivalent with experience raising for 1-5 years which is a sideline business. The seeds used are local seeds with a semi-intensive system, the feed has not met the nutritional standards and the handling or prevention of disease is almost non-existent. Chicken is sold locally.